Exploration of acupuncture therapy in the treatment of mild cognitive impairment based on the brain-gut axis theory - Jin, Yuanyuan; Hu, Fen; Zhu, Jianfang (Frontiers in Human Neuroscience, 2022)
Background Mild cognitive impairment (MCI) is an intermediary state between normal aging and dementia. Early intervention for MCI may be a key opportunity in managing dementia. Recent studies have demonstrated the alterations in the gut microbial communities associated with MCI. This study aims to evaluate if acupuncture can improve cognitive function in subjects with MCI and explore the possible mechanism of acupuncture by better defining the interactions of gut microbiota. Methods A randomized assessor-blind controlled study is proposed. A total of 62 subjects will be recruited and randomly allocated into two groups in a 1:1 ratio: the treatment and control groups. Participants in the treatment group will receive active acupuncture and exercise/cognitive training (conventional treatment). The control group will receive sham acupuncture and exercise/cognitive training. Each participant will receive active or sham acupuncture for 12 weeks. The primary outcome will be the Montreal Cognitive Assessment (MoCA) score and intestinal flora. Secondary outcomes will include mini-mental state examination (MMSE) and activity of daily living (ADL) scores. Various scales will be collected at baseline, during the treatment (week 4 and 8), week 12, and months 4 and 6 after the intervention. Feces will be collected before and after the treatment based on 16S rRNA gene sequencing technology for each participant to characterize the intestinal flora. Adverse events will be recorded by monthly follow-up. Results The trial is expected to show that cognitive function can be improved by acupuncture and produce reliable clinical outcomes in MCI patients. It will also provide preliminary data on the possible mechanism based on the changes in the intestinal flora. Collected data will be used to support future large-scale fundamental studies. Conclusions Acupuncture is an effective method to improve cognitive function for MCI. This study will provide data on the relationship between gut microbiota and the effectiveness of acupuncture in patients with MCI from a new angle. Trial registration Medical research registration information system, ID: MR-33-22-002376, https://61.49.19.26/index. Registered on 21 December 2020.